Posted by **bobpursley** on Sunday, December 10, 2006 at 9:16am.

6(4x+3)^5(4)(3x-5)^5+ 5(3x-5)^4(3)(4X+3)^6

common factors: (4x+3)^5 (3x-5)^4

[(4x+3)^5 (3x-5)^4] [24(3x-5) + 15(4x+3)]

Take the second term, combine like terms.

f(x)=(4x+3)^6(3x-5)^5 Find the derivative.

This is what I did so far.

=6(4x+3)^5(4)(3x-5)^5+ 5(3x-5)^4(3)(4X+3)^6

=24(4X+3)^5(3x-5)^5 *[(3x-5)(15)(4x+3)]

=

I am not sure what to do next. Also did I do this correctly so far?

## Answer this Question

## Related Questions

- Calc - Find the derivative of a) y=cos (x/2) b) yx-3x^2 +6 = y^4 + x a) -sin (x/...
- algebra 1 [fractions] - 8y^4+10y^3+12y+15 ----------------- 4y+5 divide then ...
- math,help - Can someone show me how step by step how to solve this problem... ...
- calculus - f(x) = 6x^2 -8x +3 how would I find the most general antiderivative ...
- Maths - 1..The first 2 terms of a geometric progression are the same as the ...
- Calc I - if f(t)=sqrt(4t+1) find f''(2) I got the first derivative to be: 1/2(4t...
- Algebra - I am stuck, pleas help, i have the example but I am still not able to ...
- Calculus - If x = t^2 + 1 and y = t^3, then d^2y/dx^2 = I know I can solve for t...
- Math - 1) If the sum of the first n terms of a series is Sn where Sn=2nē-n, (a)...
- math - 1) If the sum of the first n terms of a series is Sn where Sn=2nē-n, (a)...